Pengaruh Circuit Training menggunakan Musik terhadap Kebugaran Jasmani dan Mood State Siswa Sekolah Dasar - Muhammad Rizky Gustiansyah; Ricky Wibowo; Gano Sumarno (Jurnal Porkes, 2026)
This study was motivated by the low levels of physical fitness and mood instability among elementary school students in physical education classes. The purpose of this study was to analyze the effect of circuit training accompanied by music on the physical fitness and mood of elementary school students compared to conventional instruction. The method used was a quasi-experimental study with a pretest-posttest control group design. The study sample consisted of 56 fifth-grade students from SDN 138 Gegerkalong Girang, Bandung City, who were divided into an experimental group and a control group, each comprising 28 students, through total sampling. Physical fitness was measured using the Nusantara Student Fitness Test (TKPN), and mood state was assessed using the Brief Mood Introspection Scale (BMIS). The experimental group underwent 10 circuit training sessions accompanied by music at a tempo of 140 BPM. The results showed a significant difference in physical fitness between the groups (p=0.026<0.05), with the experimental group’s N-Gain of 0.58 (moderate) being higher than the control group’s 0.26 (low). Mood state also showed a significant difference (p = 0.000 < 0.05), with an N-Gain of 0.376 (moderate) compared to 0.099 (low). In conclusion, circuit training accompanied by music proved to be more effective than conventional learning in improving the physical fitness and mood state of elementary school students.